Pengaruh Brand Ambassador dan Brand Image terhadap Purchase Intention Produk Kecantikan Lokal pada E-Commerce Shopee - Revilla Dwiayu Nastiti Montiaque; Yoki Muchsam; Ziyadi Ali Ikromi (MANABIS: Jurnal Manajemen dan Bisnis, 2026)
The study is expected to help entrepreneurs develop successful and efficient digital marketing strategies, focusing on using Brand Ambassador and the enhancement of Brand Image on e-commerce platforms. The search aims to analyze the influence of Brand Ambassadot and Brand Image on Purchase Intention of Azarine bauty products on Shopee Platform, both individually and simultaneously. The study employs a quantitative approach with a survey method. Data were collected from 100 Shopee users in Klapanunggal District through Likert Scale questionnaire and analyzed using Multiple Linier Regression. Primary data were obtained online via Google Form, whie secondary data were drawn from various literature sources. The dependent variable is Purchase Intention (Y), while the independent variable examined Brand Ambassador (X1) and Brand Image (X2). Data management this study includes Descriptive Analysis, Instrument Testing, Multiple Linier Regression, Classical Assumption Testing, and Hypothesis Testing. The results shoes dad Brand Ambassador and Brand Image have a positive and significant effect on Purchase Intention. The findings emphasize the importance of selecting public figure and strengthening Brand Image in increasing consumer buying interest on e-commerce platforms. The study demonstrates that high-quality Brand Ambassador and Brand Image positively impact consumers Purchase Intention to make purchases.